An Engineered Thermostable Laccase with Great Ability to Decolorize and Detoxify Malachite Green - Guotao Mao (MDPI AG, 2021)
Laccases can catalyze the remediation of hazardous synthetic dyes in an eco-friendly manner, and thermostable laccases are advantageous to treat high-temperature dyeing wastewater. A novel laccase from Geothermobacter hydrogeniphilus (Ghlac) was cloned and expressed in Escherichia coli. Ghlac containing 263 residues was characterized as a functional laccase of the DUF152 family. By structural and biochemical analyses, the conserved residues H78, C119, and H136 were identified to bind with one copper atom to fulfill the laccase activity. In order to make it more suitable for industrial use, Ghlac variant Mut2 with enhanced thermostability was designed. The half-lives of Mut2 at 50 °C and 60 °C were 80.6 h and 9.8 h, respectively. Mut2 was stable at pH values ranging from 4.0 to 8.0 and showed a high tolerance for organic solvents such as ethanol, acetone, and dimethyl sulfoxide. In addition, Mut2 decolorized approximately 100% of 100 mg/L of malachite green dye in 3 h at 70 °C. Furthermore, Mut2 eliminated the toxicity of malachite green to bacteria and Zea mays. In summary, the thermostable laccase Ghlac Mut2 could effectively decolorize and detoxify malachite green at high temperatures, showing great potential to remediate the dyeing wastewater.